Improving Students’ Ability in Writing Procedure Text by Using Project-Based Learning at Second Grade Students of SMA Swasta Al-Washliyah Tanjung Morawa - Intan Sari; Nurhafni Siregar; Wariyati (Medan Resource Center, 2023)
This research was conducted to improve students' ability in writing procedure text using project-based learning. The formulation of the problem is: “Does the use of project-based learning improve the students' ability in writing procedure text”. The aims of the research is: “To find out whether the use of project-based learning improves the students' ability in writing procedure text”. In this research, the subject of the research were the grade XI-1 students at SMA Al-Washliyah Tanjung Morawa in 2021/2022 academic years which consists of 30 students. In carrying out this research, the researcher used classroom action research (CAR) as a research method. The researcher used the Kemmis and Mc Taggart model. The researchers and English teachers collaborated onthis research. Researchers as teachers and teachers as observers. This research was carried out based on research procedures, namely planning, action, observation, and reflection. This research consisted of two cycles. One cycle consisted of two meetings.The instruments used for get data were interview guidelines, questionnaire, test, and field notes. To analyze student scores, the mean of students, the class percentage, and percentage of students' improvement formulas are used. The results of the research using project-based learning showed that there was an increase in students' ability in writing procedure text. Students get grades gradually until students get good grades. The minimum completeness criteria score (KKM) in English subjects is 75. The average score of students on the pre-test is 61.13. The average score of students in post-test one is 69.06 and there are 40% of students who can get the KKM score. The students' mean score on post-test two was 78.4. And there are 83.3% of students who can get the KKM score. This means that the research has succeeded in achieving the success criteria, namely 75% of students get the KKM score. In addition, there were very positive responses from students and teachers regarding the use of project-based learning.So, it can be concluded that project-based learning can improve students' ability in writing procedure text